Characteristics and trends of hillside urbanization in China from 2007 to 2017. (February 2022) - Yang, Chao; Guo, Wenhao; Zhang, Chenchen; Cui, Aihong; Li, Xuecao; Zhao, Tianhong; Liu, Huizeng; Shi, Tiezhu; Xu, Gang; Fang, Xu; Liu, Xu; Zhang, Kangyong; et al.
Abstract: China's rapid urbanization has resulted in a dramatic loss in cultivated land that threatens future food security. Local and central government have successively launched a series of Low-slope Hilly Regions Comprehensive Development and Utilization (LHRCDU) pilot projects (i.e., the rudiment of China's hillside urbanization) since 2006 to balance the contradiction between urban growth and flat farmland protection. However, the process, quantity and effect of hillside urbanization over China remain unknown. In this study, we conducted an investigation of hillside urbanization (mainly refers to the urban land expansion on hillsides) over China from 2007 to 2017 by combining earth observation satellite data with spatial analysis techniques. Our results revealed that 12.32% of China's urban expansion area came from hillside urbanization, in which Guizhou, Yunnan, Shanxi and Fujian had large areas of hillside urbanization area (accounting for 25.63% of the total hillside urbanization area in China), while Guizhou, Tibet, Yunnan, Chongqing, Hong Kong and Shanxi had higher hillside urbanization rates (>30%). China's hillside urbanization rate also showed a steady upward trend, and 20% of hillside urbanization was high environmental cost (HEC), occupying 1535.94 km 2 of hillside forest. Our findings provide timely and transparent monitoring on China's hillside urbanization, and indicate that hillside urbanization can relieve the pressure of urban development on flat farmland but needs to be regulated for ecological safety. Highlights: 12.32% of China's urban growth area came from hillside urbanization. The hillside urbanization rate showed a steady upward trend in China. 20% of hillside urbanization was the HEC type in China. Hillside urbanization showed obvious spatial heterogeneity in China.